Expression of CYP2E1 gene in paint workers occupationally exposed to organic solvents - Thi Hien, Nguyen; Thi Cam Nhung, Do; Phu Hung, Nguyen; Phuong Thuan, Bui; Quang Huy, Nguyen (VNU Journal of Science: Natural Sciences and Technology, 2019)
Benzene (B), toluene (T), ethylbenzene (E) and xylene (X) are used commonly in paint industry, so workers who are a high risk of exposure to organic solvent (VOCs). CYP2E1 gene encodes CYP2E1 which plays an important role in the metabolism and bio-activation of volatile organic compounds. When workers expose to VOCs, their body will have a mechanism to metabolize the toxic. The enhancement of mRNA expression of CYP2E1 is a very sensitive and accurate biological marker, which is the basis for the next study to propose the level of mRNA expression of CYP2E1 gene as a human biological indicator to monitor to workers occupationally exposed to VOCs. In this study, we studied the level of mRNA expression of CYP2E1 gene from 118 participants that including 73 workers of exposed group from the paint factories and 45 workers of non-exposed group from garment factories by using Realtime-PCR with SYBR Green – an asymmetrical cyanine dye used as a nucleic acid stain in molecular biology. The initial results, showed that the exposed group had a higher mRNA expression level of CYP2E1 than the non-exposed group approximately 10.47 times, and this difference was statistically significant (P value < 0.05). And the age and the duration of exposure to organic solvents do not affect the expression level of CYP2E1 . Keywords CYP2E1, the metabolisms of volatile organic compounds, mRNA expression of CYP2E1. References [1] A. Mendoza-Cantu, F. Castorena-Torres, M. Bermudez De Leon et al., Occupational toluene exposure induces cytochrome P450 2E1 mRNA expression in peripheral lymphocytes, Environmental Health Perspectives, 114 (2006) 494 - 499. https://doi.org/10.1289/ehp.8192. [2] J.H. Hartman, G. Boysen and G.P. Miller, CYP2E1 metabolism of styrene involves allostery, Drug Metabolism and Disposition, 40 (2012) 1976-1983. https://doi.org/10.1124/dmd. 112.046698. [3] S.M. Zhu, X.F. Ren, J.X. Wan et al., Evaluation in vinyl chloride monomer (VCM) - exposed workers and the relationship between liver lesions and gene polymorphisms of metabolic enzymes, World Journal of Gastroenterology,11 (2005) 5821 -5827. 10.3748/wjg.v11.i37.5821. [4] J. Wan, J. Shi, L. Hui et al., Association of genetic polymorphisms in CYP2E1, MPO, NQO1, GSTM1, and GSTT1 genes with benzene poisoning, Environmental Health Perspectives, 110 (2002), 1213-1218. https://doi.org/10.1289/ ehp.021101213. [5] U. Bernauer, B. Vieth, R. Ellrich et al., CYP2E1 - dependent benzene toxicity: the role of extrahepatic benzene metabolism, Archives of Toxicology, 73 (1999) 189 -196. https://doi.org/ 10.1007/s002040050605. [6] P.L. Sheets, G.S. Yost and G.P. Carlson. Benzene metabolism in human lung cell lines BEAS‐2B and A549 and cells overexpressing CYP2F1, Journal of Biochemical and Molecular Toxicology, 18 (2004) 92-99. https://doi.org/10. 1002/jbt.20010. [7] V. Nedelcheva, I. Gut, P. Souček et al., Metabolism of benzene in human liver microsomes: individual variations in relation to CYP2E1 expression, Archives of Toxicology, 73 (1999) 33-40. https://doi.org/10.1007/s0020400 50583. [8] W. Tassaneeyakul, D.J. Birkett, J.W. Edwards et al., Human cytochrome P450 isoform specificity in the regioselective metabolism of toluene and o-, m-and p-xylene, Journal of Pharmacology and Experimental Therapeutics, 276 (1996) 101 - 108. 10.1163/2211730x96x00063 [9] A.-H. Wang, S.-M. Zhu, Y.-L. Qiu et al., CYP2E1 mRNA expression, genetic polymorphisms in peripheral blood lymphocytes and liver abnormalities in Chinese VCM-exposed workers, International Journal of Occupational Medicine and Environmental Health, 21 (2008), 141 - 146. 10.2478/v10001-008-0016-x. [10] J. Zhang, Y. Lihong, G. Liang et al., Detection of CYP2E1, a genetic biomarker of susceptibility to benzene metabolism toxicity in immortal human lymphocytes derived from the Han Chinese population, Biomedical and Environmental Sciences, 24 (2011) 300-309. https://doi.org/10. 3967/0895-3988.2011.03.014 [11] American Conference of Industrial Hygienists, Guide to Occupational Exposeure Values, ACGIH, Cincinnati, 2018. [12] Bộ Y Tế, Quyết định của Bộ trưởng Bộ Y tế về việc ban hành 21 tiêu chuẩn vệ sinh lao động, 05 nguyên tắc và 07 thông số vệ sinh lao động, 2002. [13] American Conference of Industrial Hygienists, Threshold Limit Value for Chemical Substances and Physical Agents and Biological Exposure Indices, ACGIH, Cincinnati, 2018. [14] Bộ Y Tế, Thông tư 28/2006/TT- BYT hướng dẫn quản lý bệnh bệnh nghề nghiệp, 2016. [15] M. Al Zallouha, Y. Landkocz, J. Brunet et al., Usefulness of toxicological validation of VOCs catalytic degradation by air-liquid interface exposure system", Environmental Research, 152 (2017) 328-335. https://doi.org/10.1016/j.envres. 2016.10.027